Hubungan Antara Kemiskinan dan Pertumbuhan Ekonomi di Provinsi Sulawesi Barat: Pendekatan Vector Autoregresive (VAR) - Nabila, Luthfannisa Afif; Desviona, Nayla; Latif, Ikhsan Abdul (Jurnal EMT KITA, 2024)
This research aims to analyze the relationship between poverty and regional economic growth in West Sulawesi province. Using panel data from five city/districts during the 2011-2022 period, the analysis model applied is vector autoregressive which is then equipped with a Granger causality test. The study results reveal that economic growth significantly reduces poverty levels. On the other hand, the poverty rate does not affect economic growth. The results of the Granger causality test reveal the existence of one-way causality from economic growth to poverty. The poverty rate responds to changes in economic growth. On the other hand, economic growth does not respond to changes in poverty rate. This finding has the implication that increasing economic growth is very important when regional governments of west sulawesi province effort to reduce poverty rate.